Apgar-score in children prenatally exposed to antiepileptic drugs: a population-based cohort study. Issue 9 (10th September 2015) - Christensen, Jakob; Pedersen, Henrik Søndergaard; Kjaersgaard, Maiken Ina Siegismund; Parner, Erik Thorlund; Vestergaard, Mogens; Sørensen, Merete Juul; Olsen, Jørn; Bech, Bodil Hammer; Pedersen, Lars Henning
Abstract : Objectives: It is unknown if prenatal exposure to antiepileptic drugs (AEDs) increases the risk of low Apgar score in offspring. Setting: Population-based study using health registers in Denmark. Participants: We identified all 677 021 singletons born in Denmark from 1997 to 2008 and linked the Apgar score from the Medical Birth Register with information on the women's prescriptions for AEDs during pregnancy from the Danish Register of Medicinal Product Statistics. We used the Danish National Hospital Registry to identify mothers diagnosed with epilepsy before birth of the child. Results were adjusted for smoking and maternal age. Results: Among 2906 children exposed to AEDs, 55 (1.9%) were born with an Apgar score ≤7 as compared with 8797 (1.3%) children among 674 115 pregnancies unexposed to AEDs (adjusted relative risk (aRR)=1.41 (95% CI 1.07 to 1.85). When analyses were restricted to the 2215 children born of mothers with epilepsy, the aRR of having a low Apgar score associated with AED exposure was 1.34 (95% CI 0.90 to 2.01) When assessing individual AEDs, we found increased, unadjusted RR for exposure to carbamazepine (RR=1.86 (95% CI 1.01 to 3.42)), valproic acid (RR=1.85 (95% CI 1.04 to 3.30)) and topiramate (RR=2.97 (95% CI 1.26 to 7.01)) when compared to unexposed children. Conclusions: Prenatal exposure to AEDs was associated with increased risk of being born with a low Apgar score, but the absolute risk of a low Apgar score was <2%. Risk associated with individual AEDs indicate that the increased risk is not a class effect, but that there may be particularly high risks of a low Apgar score associated with certain AEDs.